PROJECT BASED LEARNING (PBL) TO IMPROVE PSYCHOMOTORIC SKILLS: A CLASSROOM ACTION RESEARCH - Sumarni, W.; Wardani, S.; Sudarmin, S.; Gupitasari, D. N. (Jurnal Pendidikan IPA Indonesia, 2016)
This paper discusses the application of project-based learning (PBL) to improve student’ psychomotor skills and concept understanding, as well as knowing what PBL contribution to the improvement of student’ psychomotor skills in chemistry learning. The study was conducted in three cycles. Each cycle consisted of planning, implementation, observation, and reflection steps. One set of data consists of student’ psychomotor skills assesment, student’ conceptual understanding and questionnaire responses were obtained from the action research. Learning process was performed in the eleventh grade students included 37 students (10 males and 27 females) and 3 collaborators. The successful research was indicated by 85% of students achieve the mastery learning on concept understanding and well on psychomotor aspects. Data collection was performed using documentation method by questionnaire, observations, and tests. Data was analyzed quantitatively and qualitatively. The results show that all aspects of the psychomotor assessed include sets, mechanical response, complex response, adaptation, and origination were in high category. At the end of the lesson, the project assigned to students were evaluated jointly between teachers and students. The project results in the form of a series of distillation apparatus is applied to separate the natural compounds.